Fabrication of Al-based composites reinforced with Al2O3-TiB2 ceramic composite particulates using vortex-casting method - Roshan, M. R.; Taherzadeh Mousavian, R.; Ebrahimkhani, H.; Mosleh, A. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Vortex casting is one of the simplest methods of producing metal matrix composites (MMCs). However, this simple method does have some drawbacks, which reduce the mechanical properties of the produced composites. In this study, we tried to modify the process of composite production before, during, and after the casting procedure. Low-cost Al2O3-TiB2 ceramic composite particles, which produced after combustion synthesis, were used as reinforcement. These powders, which are thermodynamically stable with molten aluminum below 900 °C, were mixed with aluminum and magnesium powders before casting using ball milling and the mixed powders were injected into the molten metal (pure Al). This process was applied to enhance the wettability of ceramic particles with molten aluminum. After casting, warm equal channel angular pressing (ECAP) and hot extrusion processes were applied to investigate their effects on the mechanical properties of the final composites. It was revealed that both warm ECAP and hot extrusion have a strong influence on increasing the mechanical properties mainly due to decreasing the amount of porosities.
Keywords: Casting; Extrusion; Metal matrix composites; ECAP; Mechanical Properties